Diseño del sistema contra incendios de la empresa Ecuaquímica Portoviejo. - Intriago Moreira, Jean Fabricio (2022)
In Ecuador, preventing accidental fires in industries dedicated to the storage of flammable products and hazardous chemicals has become a priority for control entities, who seek to reduce the probability of risk based on good storage practices, safe infrastructure conditions and a fire detection and control system. When designing a fire protection system for Ecuaquímica in the city of Portoviejo, three key questions were asked: Based on the risk level of the Ecuaquímica Portoviejo agency, how should the fire protection system be designed, does Ecuaquímica have a fire protection network system installed and operational, and does the fire protection network system meet the hydraulic design and performance conditions that allow for effective firefighting capacity? For the design of the project, the analytical, inductive-deductive, descriptive, bibliographic and field research methods were used, which helped in the development of the research. Gretener's method was used to evaluate the company's structural fire risk, taking into account the following variables: building time, response times, emerging and human resources. Measurements and mathematical calculations were carried out to determine the dimensional characteristics of the firefighting system and the type of pumps according to NFPA standards. Based on the calculations made, an architectural plan was drawn up using Autocad software to visualize the implementation of the designed system in 3D, showing that all the risk areas of Ecuaquímica are protected by sprinklers and fire protection cabinets. We recommend maintaining good storage, order and cleanliness practices, which in the history of Ecuador and Ecuaquímica Portoviejo have prevented fires and workplace accidents. Keywords: extinguishing, fire, firefighting system, hydraulic pumps, sprinklers.